Optimization of Character Education in The Independent Curriculum Through the Pancasila Student Profile Strengthening Project Approach - Ratnawati, Rr. Eka; Warneri; Aunurrahman; Christiani, Yuzi Hana; Karim, Ajerin (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
Education with Pancasila values, the Merdeka Curriculum aims to create students who are not only academically skilled but also have a solid moral foundation. The method used in this research is library research. This research describes understanding in descriptive research that is scientific and inductive. The need for a curriculum that is responsive to student needs and the global environment is becoming increasingly important. The existence of Pancasila values ??in the face of the social crisis currently hitting Indonesian society, where the teaching and implementation of these values ??has been proven to have a positive impact on student behavior. In developing character education, Pancasila values ??have a central role as a moral and ethical foundation that is rooted in Indonesian culture and history.